2022
DOI: 10.1111/pcn.13338
|View full text |Cite
|
Sign up to set email alerts
|

Understanding source monitoring subtypes and their relation to psychosis: a systematic review and meta‐analysis

Abstract: Aims: Source monitoring (SM) is the metacognitive ability to determine the origin of one's experiences. SM is altered in primary psychiatric psychosis, although relationships between SM subtypes, other cognitive domains and symptoms are unclear. Our aims were to synthesize evidence comparing psychosis -with and without hallucinations-and healthy controls classifying SM subtypes by source discrimination (internal/external/reality monitoring) and stimulus modality (visual/auditory/imagined/performed).Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 92 publications
1
5
0
Order By: Relevance
“…Finally, the capacity to discriminate between self and exogenous stimulations, underpinned by CD systems, is also a central feature of source monitoring (SM), that is, the meta-cognitive ability to determine the origin of one's experiences. A recent systematic review (Damiani et al, 2022) has demonstrated a clear relationship between impaired SM performance and psychosis (including at-risk mental states), positing SM at the core of the developmental neurocognitive pathways underpinning the construction of a basic sense of self and as putative objective measure of anomalous self-experiences.…”
mentioning
confidence: 99%
“…Finally, the capacity to discriminate between self and exogenous stimulations, underpinned by CD systems, is also a central feature of source monitoring (SM), that is, the meta-cognitive ability to determine the origin of one's experiences. A recent systematic review (Damiani et al, 2022) has demonstrated a clear relationship between impaired SM performance and psychosis (including at-risk mental states), positing SM at the core of the developmental neurocognitive pathways underpinning the construction of a basic sense of self and as putative objective measure of anomalous self-experiences.…”
mentioning
confidence: 99%
“…Fornito et al, 2012; Minzenberg et al, 2009; Wheeler & Voineskos, 2014) have led to the hypothesis that SZ is a brain ‘dysconnection’ syndrome (Friston et al, 2016; Stephan et al, 2009). Therefore, there is an increasing need to investigate the pathophysiology of SZ from a network or connectome perspective (Damiani et al, 2022; Gao et al, 2023; Kitajima et al, 2023; Tagawa et al, 2022). Clinically, SZ is a debilitating psychotic disorder characterized by a heterogeneous array of symptoms, such as auditory hallucinations, delusions, disorganized thoughts, ego disturbances, passivity phenomena and cognitive deficits (Onitsuka, Hirano, Nakazawa, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…14 group contrasts for internal–external source misattributions). Given that the primary aim of the systematic review was to compare results across the range of proposed cognitive mechanisms, and that meta-analysis of source-monitoring data has been well documented (see Brookwell et al, 2013 ; Damiani et al, 2022 ; Waters et al, 2012b ), performing a quantitative synthesis for this single sub-domain was considered unsuitable. It is possible to conduct meta-analysis of broader, collapsed groups of data, with follow-up statistics to accommodate study deviations (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Previous meta-analyses, focusing on specific domains of cognition, have demonstrated moderate-to-large associations between hallucinations and a self-monitoring bias ( Waters et al, 2012b ), increased externalising source-monitoring errors ( Brookwell et al, 2013 ; Damiani et al, 2022 ) and reduced left-hemispheric language lateralisation ( Ocklenburg et al, 2013 ). Source-monitoring difficulties were observed in the context of auditory stimuli and imagined mental events ( Damiani et al, 2022 ), and identified in spite of intact broader memory function ( Waters et al, 2012b ). While such reviews have provided valuable integration of findings, some methodological inconsistencies are evident.…”
Section: Introductionmentioning
confidence: 99%